A decade of tuberculosis eradication programs in the Mediterranean water buffalo (Bubalus bubalis) in South Italy: Are we heading toward eradication? - Martucciello, Alessandra; Ottaiano, Maria; Mazzone, Piera; Vitale, Nicoletta; Donniacuo, Anna; Brunetti, Roberta; Di Franco, Marcellino; Cerrone, Pasquale; Spoleto, Claudia; Galiero, Giorgio; De Carlo, Esterina (Frontiers in Veterinary Science, 2024)
The water buffalo (Bubalus bubalis) is susceptible to bovine tuberculosis (TB), which receives increased attention in areas where buffalo breeding is prevalent, such as in Southern Italy, especially in the Campania region, where 70% of the buffalo stock is bred. Since 2012, TB testing in buffalo herds has been conducted using the Single Intradermal Test (SIT), with the Comparative Intradermal test (CIT) used in cases of inconclusive results. From 2012 to 2016, the interferongamma (IFN- test was occasionally employed experimentally in herds with TB outbreaks to expedite eradication efforts. A local TB eradication program was implemented in officially TB-free buffalo herds between 2017 and 2019. This program involves initial screening with SIT, followed by confirmatory tests, including CIT and IFN-γ, for positive reactions. Since June 2019, the IFN- test has replaced the CIT in officially TB-free herds upon positive SIT reactions. Additionally, in suspected and confirmed TB-outbreak herds, the IFN- test was used at the discretion of the competent authority. Between 2017 and 2019, approximately 295,000 buffaloes in Campania were screened annually with in vivo tests provided by TB eradication programs.During this period, 32,040 animals from 855 herds were tested using the IFN- test and 4,895 tested positive. Since 2020, the use of IFN- testing has increased, and has become a prerequisite for the acquisition of TB-free status and is being systematically applied for TB outbreak-extinction procedures. The test was performed in all breeding buffaloes in cases of doubtful SIT results in TBfree herds and when TB lesions are detected at slaughter in animals from TB-free herds. This combined approach helped detect more TB outbreaks, and thereby led to a reduction in the TB prevalence and incidence rates. By 2022, the prevalence had decreased to 1.56%, and the incidence had decreased to 0.73%, after the increased use of the IFN- test.This study highlights the effectiveness of implemented strategies in reducing TB in this region. Overall, the data demonstrate the successful impact of TB eradication measures and surveillance activities in reducing bubaline TB prevalence and incidence in the Campania region.